(untitled) (Fiep Bulletin - online, 2013)
This research had the aim of examining the dimensions of the" real "me" and the virtual body "Avatar" in Second Life through the game experience and the construction of the cyber body. Specifically, the investigative proposal craved to observe the virtual world of Second Life and the possibilities for interaction and participation in the game; to understand the meanings of the body "Me" and the body "Avatar’’ on the game’s time and space based on the dialogue between the real world and the virtual world; to investigate whether the body "Avatar" is also guided by the principles of the instrumental rationality that the body "Me" takes on the contemporary society. To this end, the virtual ethnography has guided the research’s development, with the direct insertion of the researchers in the field of the game for a period of six months. The observations were arranged in a field diary and analyzed in the light of the ethnographical orientation. This way, we have reflected on how virtual games built by individuals bring direct implications to "being" body, in real life, guided by the instrumentalization of the individual and his actions.